Dampak Membuang Sampah Sembarangan terhadap Kelestarian Lingkungan dan Ekonomi Beserta Sanksi terhadap Masyarakat yang Membuang Sampah Sembarangan Tempat (Studi Kota Bukittinggi) - Sabri, Sabri; Nasfi, Nasfi (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
With various kinds of progress in recent years, the City of Bukittinggi Government is still faced with various problems/problems, one of which is the problem of waste management and sanctions against people who dispose of littering places. This study examines the impact of littering on environmental sustainability and imposing sanctions on people who dispose of garbage carelessly "studies in the City of Bukittinggi" How not, now the waste problem is still a conversation between the community and the city government, even though Payakumbuh is a city in the region West Sumatra, but the amount of waste produced is very large, so that waste is a fairly heavy problem in this city. One of the solutions provided by the government regarding waste management is by building a Regional Final Disposal Site (TPA) and giving sanctions to people who dispose of litter.